A New Methodology for Application of Impact's Identification Using Fuzzy Relation - Roveda, J. A. F. [UNESP]; Burghi, A. C. A.; Roveda, S. R. M. M. [UNESP]; Bressane, A. [UNESP]; Franca, L. V. G. [UNESP]; Zadeh, L. A.; Yager, R. R.; Shahbazova, S. N.; Reformat, M. Z.; Kreinovich, V (Springer, 2018)
The Environmental Impact Assessment (EIA) is a mechanism used by governments and private institutions to predict environmental damage and optimize positive impacts. One of the greatest challenges of the EIA process is to achieve an effective integration of the various tools and the analytical procedures. This paper proposes a new methodology for the application of impact's identification and characterization matrices by the use of Fuzzy Logic, using specifically Fuzzy Relations Theory. Three Weight Matrices of State and Association, for each type of expertise (physical, biotic, and anthropic) were created. Fuzzy Relations to aggregate all these matrices were used, and a Weighted Response Matrix was obtained. The developed fuzzy methodology was applied to real cases of EIA, aiming to compare the results. The EIA Mario Covas Road Program-Modified Southern Section was used, and the fuzzy interaction matrix proves to be a successful tool. Because of the results, it was possible to infer that the new methodology, using fuzzy approach is an effective and practical tool in the Environmental Impact Assessment.